2021
DOI: 10.1111/jonm.13414
|View full text |Cite
|
Sign up to set email alerts
|

Curbing nurses' burnout during COVID‐19: The roles of servant leadership and psychological safety

Abstract: Aims This study examines the role of servant leadership through the mechanism of psychological safety in curbing nurses' burnout during the COVID‐19 pandemic. Background During the COVID‐19 pandemic, studies have shown an increased level of stress and burnout among health care workers, especially nurses. This study responds to the call for research to explore the mechanisms of servant leadership in predicting nurses' burnout by employing the perspective of conservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 47 publications
5
88
1
3
Order By: Relevance
“…26 Psychological safety is defined as individuals' perceptions of the consequences of taking interpersonal risks in their working place, 27 and has been shown to improve work performance, information sharing, and learning in the workplace. 28 In addition to the above, it has also been reported to be useful in preventing the deterioration of workers' mental health during the COVID-19 pandemic 29 -a finding that is consistent with our view. This study suggests that infection control practices at the working place are expected to reduce the prevalence of COVID-19 infections and are also beneficial to the workers' mental health.…”
Section: Discussionsupporting
confidence: 90%
“…26 Psychological safety is defined as individuals' perceptions of the consequences of taking interpersonal risks in their working place, 27 and has been shown to improve work performance, information sharing, and learning in the workplace. 28 In addition to the above, it has also been reported to be useful in preventing the deterioration of workers' mental health during the COVID-19 pandemic 29 -a finding that is consistent with our view. This study suggests that infection control practices at the working place are expected to reduce the prevalence of COVID-19 infections and are also beneficial to the workers' mental health.…”
Section: Discussionsupporting
confidence: 90%
“…Social, psychological, and preventive rewards were mentioned as good measures, as well as the importance of support from nursing leaders. In other instances, pandemic-related training and support were helpful to prevent infections, and servant and shared leadership was claimed to reduce burnout and psychological safety [27,[57][58][59][60][61][62][63][64][65].…”
Section: Health Crisis and Hrmmentioning
confidence: 99%
“…In crisis times, researchers have argued that servant leadership seems to be a promising leadership approach in managing health-care professionals (Jimenez et al, 2021;Ma et al, 2021). For instance, Jimenez et al (2021) indicated that the aspects of servant leadership such as empowering, caring, listening and behaving ethically are of utmost importance in the health-care sector in times of crisis such as the COVID-19 pandemic.…”
Section: Servant Leadership and Task Performancementioning
confidence: 99%
“…For instance, Jimenez et al (2021) indicated that the aspects of servant leadership such as empowering, caring, listening and behaving ethically are of utmost importance in the health-care sector in times of crisis such as the COVID-19 pandemic. Ma et al (2021) called for the adoption of servant leadership in crisis times because it demonstrates to reduce nurses' burnout in Pakistani hospitals during the pandemic. Given these results, we argue that servant leadership in a crisis context may positively contribute to task performance for the following reasons.…”
Section: Servant Leadership and Task Performancementioning
confidence: 99%
See 1 more Smart Citation